Determinación de la concentración de nutrientes N, P, K en los Residuos Sólidos Orgánicos selectivos provenientes del mercado Ayaymaman, mediante la técnica del Compostaje, Moyobamba, 2012 - Mansilla de la Peña., Marco Antonio (2013)
The research project, The concentration of nutrients N, P, K in solid organic waste from selective market ayaymaman using the technique of composting, specific objectives: Perform classification by sectors Generation of Solid Organic Waste , in the City Market ayaymaman Moyobamba; build processing Composting of Solid Organic Waste; determining concentrations of N, P, K, pH, electric conductivity and organic matter contained in the compost. The problem statement was: What is the concentration of nutrients in selective organic solid waste from ayaymaman market? The variables were: Independent Variable Xi: Branches of study. And dependent variable Yi: concentration of nutrients N, P, K, EC, pH and organic matter. The hypothesis to prove If we make compost Organic Solid Waste selective ayaymaman from the market, then the concentration of nutrients N, P, K are significant. The methodology consisted in requesting permission to Moyobamba district municipality, in coordination with the market administrator; TALK provide MERCHANT INFORMATION MARKET, Harvest was done for a week (Saturday - Sunday) discarding the first day is considered day zero; pickup schedule was from 3:00 pm. The transfer of waste was carried out in a cargo bike (van), Ecotourism Center to the "Milan", instead of the built environment (compost); the weight is carried on a balance of needle marks Libra, up to 40 Kg, the weighing is performed by components.; volume was determined with a bucket of 45 liters. The density was determined by the weight volume ratio. Moisture was determined by Method Kiln Drying. Chemical analysis of compost obtained was held at the National University of San Martin, Tarapoto, the method was for the N Kjeldahl method modified for P, the method and the colorimeter method K cremated. In the classification of sectors generating organic waste in ayaymaman market, classified according to the origin and nature: Sector foods, fruits and vegetables and juices industry sector. "Bamboo" (Guadua superba) and wood (lumber) was used for building processing composting of solid organic waste. In determining the concentrations of N, P, K, pH, organic matter and electrical conductivity containing the finally formed compost from organic solid waste market ayaymaman, was as follows When sectoral classification of generation solid organic waste in the market ayaymaman Moyobamba, the food sector, the fruits and vegetables, and juices sector said. The analysis of variance and Duncan test for organic matter content of nitrogen, phosphorus and potassium did not show statistical significance or percentage difference between the averages; however, the pH values ​​of the sectors food, witness fruits - vegetables and juices were, 10,788, 10,590, 9,952 and 8,904 respectively, the witness reached a higher electrical conductivity, with 16,376 units, and 11,872 statistical similarity. pcs., but the juice sector was 7,098 units. • The compost had a length of 03m, width and height of 01m. Were located 20 cm in height, and remained half open. The analysis of the concentrations of organic matter, N, P, K, CE and pH of the compost well trained, from the fields of organic solid waste generation, was performed at the Laboratory of soil, water and leaf of the National University of San Martin, Tarapoto. In which, the food industry organic matter was 37.80%, the fruit-vegetable industry was 25.80, the juice industry 39.60, 19.60 Witness; Nitrogen meals sector was 1.89%, fruit-vegetable sector was 1.29%, 1.98% of the juice industry and the control was 0.98%. The phosphorus in the food industry was 0.02%, fruit-vegetable industry 0.01%, 0.02% of the juice industry and the control 0.01%. Potassium foods sector was 0.07%, fruit-vegetable sector was 0.07%, the sector was 0.08% juices, the witness was 0.08%. The (EC) electrical conductivity of the sector was 19.0 meals of fruit-vegetable sector was 12.43, the juice sector was 11.00 and 15.45 respectively Witness.